Hungarian Monitoring, 11 December 1988 . [Magyar rádiófigyelő], 1988. december 11 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR will publicly withdraw its troops from Czechoslovakia, Hungary and the GDR within two years - Armenian natural catastrophe - Gorbachev's speech at the UN - Austria and Hungarian reforms Domestic Affairs: - EEC delegation in Budapest - Csongrád County Party meeting - Situation for Transylvanian refugees - What credit for "Hitel" (Credit) magazine? interview with the paper's editor-in-chief, Zoltán Bíró - First appearance of a report prepared and banned in 1970 with Júlia Rajk - Soviet troop withdrawals - Crossroads and dangers: conversation on historical and economic alternatives Külpolitika: - A SZU a teljes nyilvánosság mellett fogja kivonni csapatait Csehszlovákiából, Magyarországról és az NDK-ból - Ehhez két év szükséges - Az örményországi természeti katasztrófa - Gorbacsov ENSZ-beli beszéde - Ausztria és a magyar reformok Belpolitika: - EGK küldöttség Budapesten - Csongrád-megyei pártértekezlet - Erdélyi menekültek helyzete - Milyen a Hitel hitele? - A lap főszerkesztője, Bíró Zoltán válaszol - Egy Rajk Júliával, 1970-ben készült és letiltott riport premiere - Szovjet haderőkivonás kérdése - Válaszutak és veszélyek - Beszélgetés történelmi - És gazdasági alternatívákról